Trehalose Alleviated Salt Stress in Tomato by Regulating ROS Metabolism, Photosynthesis, Osmolyte Synthesis, and Trehalose Metabolic Pathways - Yang, Yan; Yao, Yandong; Li, Jing; Zhang, Jing; Zhang, Xiaodan; Hu, Lixia; Ding, Dongxia; Bakpa, Emily Patience; Xie, Jianming (Frontiers in Plant Science, 2022)
Trehalose plays a critical role in plant response to salinity, but the involved regulatory mechanisms remain obscure. Here, this study explored the mechanism of exogenous trehalose-induced salt tolerance in tomato plants by using the hydroponic test method. Our results indicated that 10 mM trehalose displayed remarkable plant biomass by improving growth physiology, which were supported by the results of chlorophyll fluorescence and rapid light-response curve. In the salinity environment, trehalose + NaCl treatment could greatly inhibit the decrease of malondialdehyde level, and it increases the contents of other osmotic substances, carbohydrates, K+, and K+/Na+ ratio. Meanwhile, trehalose still had similar effects after recovery from salt stress. Furthermore, trehalose pretreatment promoted trehalose metabolism; significantly increased the enzymatic activity of the trehalose metabolic pathway, including trehalose-6-phosphate synthase (TPS), trehalose-6-phosphate phosphatase (TPP), and trehalase (TRE); and upregulated the expression of SlTPS1, SlTPS5, SlTPS7, SlTPPJ, SlTPPH, and SlTRE under saline conditions. However, the transcriptional levels of SlTPS1, SlTPS5, and SlTPS7 genes and the activity of TPS enzyme were reversed after recovery. In addition, we found that hydrogen peroxide (H2O2) and superoxide anion (O2−) were accumulated in tomato leaves because of salt stress, but these parameters were all recovered by foliar-applied trehalose, and its visualization degree was correspondingly reduced. Antioxidant enzyme activities (SOD, POD, and CAT) and related gene expression (SlCu/Zn-SOD, SlFe-SOD, SlMn-SOD, SlPOD, and SlCAT) in salt-stressed tomato leaves were also elevated by trehalose to counteract salt stress. Collectively, exogenous trehalose appeared to be the effective treatment in counteracting the negative effects of salt stress.